Genomic analysis of low‐grade serous ovarian carcinoma to identify key drivers and therapeutic vulnerabilities. Issue 1 (28th October 2020) - Cheasley, Dane; Nigam, Abhimanyu; Zethoven, Magnus; Hunter, Sally; Etemadmoghadam, Dariush; Semple, Timothy; Allan, Prue; Carey, Mark S; Fernandez, Marta L; Dawson, Amy; Köbel, Martin; Huntsman, David G; et al.
Abstract: Low‐grade serous ovarian carcinoma (LGSOC) is associated with a poor response to existing chemotherapy, highlighting the need to perform comprehensive genomic analysis and identify new therapeutic vulnerabilities. The data presented here represent the largest genetic study of LGSOCs to date ( n  = 71), analysing 127 candidate genes derived from whole exome sequencing cohorts to generate mutation and copy‐number variation data. Additionally, immunohistochemistry was performed on our LGSOC cohort assessing oestrogen receptor, progesterone receptor, TP53, and CDKN2A status. Targeted sequencing identified 47% of cases with mutations in key RAS/RAF pathway genes ( KRAS, BRAF, and NRAS ), as well as mutations in putative novel driver genes including USP9X (27%), MACF1 (11%), ARID1A (9%), NF2 (4%), DOT1L (6%), and ASH1L (4%). Immunohistochemistry evaluation revealed frequent oestrogen/progesterone receptor positivity (85%), along with CDKN2A protein loss (10%) and CDKN2A protein overexpression (6%), which were linked to shorter disease outcomes. Indeed, 90% of LGSOC samples harboured at least one potentially actionable alteration, which in 19/71 (27%) cases were predictive of clinical benefit from a standard treatment, either in another cancer's indication or in LGSOC specifically. In addition, we validated ubiquitin‐specific protease 9X (USP9X), which is a chromosome X‐linked substrate‐specific deubiquitinase and tumour suppressor, as a relevant therapeutic target for LGSOC. Our comprehensive genomic study highlighted that there is an addiction to a limited number of unique 'driver' aberrations that could be translated into improved therapeutic paths. © 2020 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.